Human Resource Development Strategy for Improving Employee Performance at PT. Bintanindo Sukses Perkasa - Hoirun Nisak; Novia Aryanti; Rianty Muhammad; Yessa Aulia Taufina Fredi; Satriadi Satriadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Human resource development for employees is to improve the productivity and overall performance of the organization. This is due to the recognition of the important role of human resource development in achieving organizational goals. Therefore, this study investigates the human resource development strategy on employee performance at PT. Bintanindo Sukses Perkasa. This study uses a qualitative approach with a descriptive method to describe in detail the phenomena that occur and analyze the problems that exist in the context of improving employee performance through human resource development strategies at PT. Bintanindo Sukses Perkasa. The results of the study indicate that the human resource development strategy at PT. Bintanindo Sukses Perkasa includes training held by the company, including Project Skill Training, Finance Skill Training, Legal and HRD Skill Training, and Admin Skill Training. With the development of human resources, there is a significant increase in employee performance.